2019
DOI: 10.11646/zootaxa.4586.2.3
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Lycodon Boie, 1826 (Serpentes: Colubridae) from Thanh Hoa Province, Vietnam 

Abstract: We describe a new species of the genus Lycodon based on an adult male specimen from Thanh Hoa Province, Vietnam. Lycodon namdongensis sp. nov. is differentiated from its congeners by a combination of the following characters: dorsal scales in 17−17−15 rows, all smooth; supralabials 8; infralabials 10; one large loreal on each side, separated from the eye; cloacal single; ventral scales 218 (plus two preventral scales); subcaudals 85, paired; a total length of 723 mm; tail / total length ratio 0.205; dorsal hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 817 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…MP analysis resulted in five most parsimonious trees having 1662 steps (CI = 0.41, RI = 0.72). Our tree topologies are very similar to those recovered by Guo et al (2015) and Luu et al (2018). The new species was recovered to be the sister species to a clade containing L. multizonatus + L. liuchengchaoi , with strong support in BI (PP = 96), but weak support in MP and ML (BP MP = 56, BP ML = 69) (Fig.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…MP analysis resulted in five most parsimonious trees having 1662 steps (CI = 0.41, RI = 0.72). Our tree topologies are very similar to those recovered by Guo et al (2015) and Luu et al (2018). The new species was recovered to be the sister species to a clade containing L. multizonatus + L. liuchengchaoi , with strong support in BI (PP = 96), but weak support in MP and ML (BP MP = 56, BP ML = 69) (Fig.…”
Section: Resultssupporting
confidence: 75%
“…PCR conditions were 95 °C for 15 minutes to activate the Taq, with 40 cycles of 95 °C for 30 s, 45 °C for 45 s, 72 °C for 60 s, and a final extension at 72 °C for six minutes. The mitochondrial cytochrome b gene was utilised in this study because it has been widely used in previous molecular analyses of Lycodon (e.g., Guo et al 2013, Siler et al 2013), and has been shown to be informative in revealing new species of Lycodon (e.g., Grismer et al 2014, Luu et al 2018, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A tissue sample was collected from the holotype of Lycodon pictus (IEBR 4166) then extracted following formalin protocol developed by Friedman &Desalle (2008) using GTE andNeang et al, 2014). From Vietnam, sixteen species of Lycodon have been reported to date, comprising L. capucinus (Boie, 1827), L. cardamomensis (Daltry & Wü ster, 2002), L. davisonii (Blanford, 1878), L. fasciatus (Anderson, 1879), L. fl avozonatus (Pope, 1928), L. futsingensis (Pope, 1928), L. laoensis Gü nther, 1864, L. meridionalis (Bourret, 1935), L. namdongensis Luu, Ziegler, Ha, Le & Hoang, 2019, L. paucifasciatus Rendahl in Smith, 1943, L. pictus Janssen, Pham, Ngo, Le, Nguyen & Ziegler, 2019 (Hu & Zhao, 1972[1975), L. rufozonatus Cantor, 1842, L. ruhstrati abditus Vogel, David, Pauwels, Sumontha, Norval, Hendrix, Vu & Ziegler, 2009, L. septentrionalis (Gü nther, 1875 and L. subcinctus Boie, 1827(Uetz et al, 2020. The last description from Vietnam was that of Lycodon pictus based on a type series collected from Cao Bang Province, northern Vietnam.…”
Section: Molecular Analysismentioning
confidence: 99%